Efeito in vitro de vernizes fluoretados contendo NaF e TiF4 nas propriedades nanomecânicas e de superfície do esmalte dentário submetido à erosão - Medeiros, Maria Isabel Dantas de (2014)
Objectives: To analyze the effect of NaF and TiF4 varnishes on nanohardness (N) and elastic modulus (E) of enamel surface after very short exposure time to simulation of drinking a can of soft drink; and evaluate the thickness and topography of protective layer formed, by atomic force microscopy (AFM). Methods: Thirty blocks of human enamel (4x4 mm) were divided into 3 groups (n=10): control, NaF varnish and TiF4 varnish. The specimens remained in artificial saliva for 24h, and the varnishes were applied only once. After 6h, specimens were submitted to erosive challenge (10 cycles: 5s in cola drink/5s in artificial saliva). The thickness of protective layer formed and the surface topography were evaluated by optical microscope and AFM. The data were subjected to Two-Way ANOVA, Tukey and Student s-t (α=0.05). Results: The values shown for N and E (GPa) before and after erosive challenge differed statistically, only for control and TiF4 groups. After the erosive challenge, NaF group showed statistically higher values for N and E than those found for control and TiF4 groups. However, the thickness and depth of indentation values showed that N and E values found for TiF4 group were related to the protective layer formed. By AFM, both varnishes showed globular protective layer formation, and the thickness of layer was significantly higher for TiF4 than NaF group. Conclusions: NaF varnish was able to protect the nanomechanical properties of enamel after short erosive challenge, and TiF4 varnish showed a thick and homogeneous protective layer formation with nanomechanical properties. Keywords: tooth erosion; elastic modulus; fluorides; microscopy, atomic force